The Adaptation of the Carbohydrate Counting Method Affects HbA1c and Improves Anthropometric Indicators in Patients With Diabetes Mellitus 2 - Di Iorio, Adriana Beatriz; Orozco Beltrán, Domingo; Quesada Rico, José Antonio; Carratalá Munuera, María Concepción (Frontiers, 2021)
The worldwide growth of diabetes mellitus (DM) has, in recent years, generated an exponential increase in associated comorbidities such as high blood pressure, cholesterol, and cardiovascular risk (CVR), with an increase in mortality in the population (1). At the same time, the global DM pandemic increased by 75% in recent decades, with a large proportion of affected individuals spanning all age groups from 1988 to 2010 (2). In the Americas, its prevalence has increased from 5 to 8.3% in recent years, particularly in Honduras, where 6% of individuals over 20 years of age have DM (3). As such, DM increases health care costs in low- and middle-income nations (4). Diagnosing diabetes mellitus type 2 (DM2) has changed since the inclusion of glycosylated hemoglobin (HbA1-c), as it is ¿6.5% in DM2. The criterion for fasting glucose is ¿126 mg/dL, whereas glucose at 2 h is ¿200 mg/dL (5). A hyperglycemic state can lead to an underlying prothrombotic environment, an overactivation of the coagulation cascade, fatal thromboembolic complications, and, eventually, increased mortality in DM patients (6). Medical treatment focuses on three pillars: drugs, nutrition, and education (7). The use of metformin acts as a standard pharmacological insulin used by patients to avoid weight gain (8). Nutritional medical therapy (NMT) prioritizes glycemic control and reduces comorbidities (7, 9). The diet promotion program is based on dietary guidelines, with group physical activity proving effective for predicting DM2 sowing but ineffective for long term benefits due to the lack of adherence (10). To this effect, the American Diabetes Association emphasized the need for individualized medical nutritional therapy (IMNT) (11). Carbohydrate counting (CCHO) has been shown to be effective for glycemic control in diabetes mellitus type 1 patients when being intensively treated with insulin (12, 13). Carbohydrate counting considers the actual content of food consumed based on the individual¿s usual intake and coordinates insulin-glucose utilization so that both curves act as a single exponentially flattened growth curve (14). The resulting weight gain is a consequence of decreased urine sugar loss (15). Few studies have used carbohydrate counting in DM2 in the primary care setting, and although it showed improvements in HbA1c, compression of carbohydrate counting was considered difficult for participants (16). Given the paucity of evidence from randomized controlled clinical trials in Latin American for carbohydrate counting DM2 patients, this work aimed to evaluate the effectiveness of this medical nutritional treatment, which minimizes the risk of developing comorbidities and public spending on health care